Glutamine Cooperatively Upregulates Lipopolysaccharide-Induced Nitric Oxide Production in BV2 Microglial Cells through the ERK and Nrf-2/HO-1 Signaling Pathway - Jayasooriya, Rajapaksha Gedara Prasad Tharanga (Antioxidants (Basel), 2020)
Glutamine (Gln) is a nonessential α-amino acid for protein biosynthesis. However, the mechanism through which Gln regulates NO production in microglial cells is still unclear. In this study, we investigated whether the presence or absence of Gln affects NO production in lipopolysaccharide (LPS)-stimulated BV2 microglial cells. Our data revealed that Gln depletion decreased cell viability accompanied by mild cytotoxicity, and blocked LPS-induced NO production concomitant with a significant decrease in inducible NO synthase (iNOS) expression. Additionally, Gln depletion for 24 h blocked the restoration of LPS-mediated NO production in the presence of Gln, suggesting that Gln depletion caused long-term immune deprivation. In particular, sodium-coupled amino acid transporter 1 and 2 (SNAT1 and SNAT2), which are the main Gln transporters, were highly upregulated in LPS-stimulated BV2 microglial cells, in the presence of Gln accompanied by NO production. Regardless of the presence of Gln, LPS positively stimulated nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) expression, and transient Nrf2 knockdown and HO-1 inhibition stimulated LPS-induced NO production and iNOS expression; however, transient Nrf2 knockdown did not affect SNAT1 and SNAT2 expression, indicating that Gln transporters, SNAT1 and SNAT2, were not regulated by Nrf2, which downregulated the HO-1-mediated NO production. Moreover, Gln depletion significantly reduced LPS-induced extracellular signal-regulated kinase (ERK) phosphorylation; furthermore, a specific ERK inhibitor, PD98059, and transient ERK knockdown attenuated LPS-stimulated NO production and iNOS expression, in the presence of Gln, accompanied by downregulation of SNAT1 and SNAT2, suggesting that the ERK signaling pathway was related to LPS-mediated NO production via SNAT1 and SNAT2. Altogether, our data indicated that extracellular Gln is vital for NO production from microglia in inflammatory conditions.